Carotid Artery Occlusive Disease—Clinical Considerations in Surgical Revascularization - Tolley, John A. (1967)
In clinical evaluation and analysis of 85 consecutive carotid endarterectomies in 74 consecutive patients, the operation was shown to be an effective and safe method of treating cerebral vascular insufficiency. It must be properly timed and performed, and excellent results may be expected, particularly in comparison with nonoperatively treated patients with the same disease.